Dimensionen eines Verbrechens/Dimensions of a Crime: Sowjetische Kriegsgefangene im Zweiten Weltkrieg/Soviet Prisoners of War in World War II - Deutsch-Russisches Museum Berlin-Karlshorst; Blank, Margot; Quinkert, Babette (Metropol Verlag, 2021)
The German Reich attacked the Soviet Union on June 22, 1941. By the end of the war the German Army made prisoners of about 5.7 million Red Army soldiers. More than three million of them perished in German custody. Although they are one of the largest categories of victims of German mass crimes, they are hardly commemorated to this day. The catalogue documents the traveling exhibition of the same name, which aims to bring the history of the Soviet prisoners of war closer to a broad public. Essays also offer in-depth insights into individual topics.